Limosilactobacillus reuteri with menaquinone-7 improves bone biomechanics and microarchitecture in ovariectomized mice: preliminary study - Santos, Thaís Aguiar [UNESP]; Ribeiro, Jaqueline Lemes [UNESP]; Battistelli, Luisa Souza [UNESP]; Anbinder, Ana Lia [UNESP] (Springer Nature, 2025)
AimThis study aimed to evaluate the effects of Limosilactobacillus reuteri (LR) and its combination with menaquinone-7 (MK-7; K) on ovariectomy-induced bone loss in mice and on bacterial growth in vitro.MethodsIn the in vivo study, animals were divided into five groups: sham-operated (SHAM); ovariectomy (OVX); OVX-LR; OVX-K; OVX-LR-K. After 4 weeks of treatment, femur cortical biomechanical properties, vertebral microarchitecture, osteocalcin levels, Occludin and Jam3 expression, and intestinal histomorphometry were evaluated. In vitro, microbial growth was assessed by incubating L. reuteri with MK-7. After incubation, optical densities were measured, and bacteria were cultured on MRS agar for the colony-forming unit (CFU/ml) counting.ResultsL. reuteri, MK-7, and their combination significantly improved femur intrinsic biomechanical properties and cortical vertebral thickness. The combined treatment exhibited a synergistic effect on the modulus of elasticity, and increased cortical vertebral volume and the villus/crypt ratio in comparison to OVX. L. reuteri and its combination with MK-7 restored vertebral trabecular microarchitecture values to SHAM levels. However, no significant differences were observed in serum levels of osteocalcin, Occludin or Jam3 expression among groups. In vitro, a significant increase in optical density and viable cell count was observed after 4 h of incubation.ConclusionL. reuteri and its combination with MK-7 improved bone biomechanical and microarchitecture properties. We propose a synergistic preventive action of L. reuteri and MK-7 in estrogen-deficient mice. Additionally, the enhanced survival of L. reuteri in the presence of MK-7 may partially explain the observed benefits of the combined treatment in vivo.